A win or a flop? Measuring mass protest successfulness in authoritarian settings. (January 2023) - Turner, Kimberly
Previously rare events, mass protest movements have become popular vehicles for those seeking political, economic, and social change. How do we evaluate movement success? Most studies addressing movement outcomes are grounded in the goal attainment approach, where movement success is dependent upon fulfilling one's stated demands. The models derived from this approach heavily rely on visibility and transparency in the policymaking process. These offer limited analytical utility for scholars studying movements in authoritarian states, where policymaking is shrouded and media is state-controlled. Evaluating movements solely on their fulfillment of mission goals is highly problematic, as movements produce more outcomes than their intended goals. Movements also produce unintended benefits: concessions unrelated to the movement's mission. These include negative consequences, or societal costs. Since movements produce both positive and negative unintended outcomes, any evaluation of a movement should also incorporate the costs associated with new gains. I argue a cost–benefit approach improves scholarly conceptualization and measurement of protest success. I conceptualize protest success as multidimensional and comprised of protest gains and societal costs. I develop a 21-point scale of protest success using Mokken Scale Analysis. AISP diagnostics indicate gains and costs comprise separate subscales, which are collapsed to produce total sum scores. I score 34 nonviolent movements in authoritarian states between 2002 and 2013 on an additive scale. Protests in authoritarian settings attain considerable accomplishments; however, those gains come with significant cost. Most total success scores are negative, indicating considerable backlash is common during and immediately after the demobilization of movements in authoritarian states. Success scores improve upon the canonical binary measure by: (1) offering improved discrimination between movements, (2) identifying cases of regime 'ignoring', and (3) pinpointing misclassified cases. By incorporating negative consequences into our evaluations, we advance our understanding why movements deemed successful by scholars are disappointments to their home publics.